The efficacy of single-session solution-focused therapy on the level of self-compassion, forgiveness, and marital conflict of married women - Arezou Ahangar; Sedigheh Ahmadi; Esmaeil Asadpour; Maryam Moghadasin (مجله علوم روانشناختی)
Background: Self-compassion refers to the degree of compassion one feels towards oneself in response to shortcomings or failures, and it is linked with reduced anxiety and increased life satisfaction. Numerous studies have shown the effectiveness of various psychological therapies in influencing levels of self-compassion, forgiveness, and marital conflict among married women. However, there is a research gap in the area of solution-focused single-session therapy and psychological issues affecting married women, who constitute a significant segment of society. Aims: This study aimed to investigate the effectiveness of solution-focused single-session therapy on levels of self-compassion, forgiveness, and marital conflict among married women. Methods: This was an applied research using a single-subject experimental design, specifically the Multiple Baseline Across Subjects (ABA) design. The research population comprised all married women experiencing marital conflicts in Tehran in the year 2023. Participants were recruited voluntarily through announcements. After applying screening criteria, five individuals were selected and underwent baseline, intervention, and follow-up phases. Participants completed the Self-Compassion Scale (Neff, 2003), the Interpersonal Forgiveness Scale (Paleari et al., 2009), and the Marital Conflict Questionnaire (Senaie et al., 2008). Results: The results of this study indicated that solution-focused single-session therapy led to a significant increase in the average percentage of improvement in self-compassion and forgiveness, as well as a decrease in the average percentage of improvement in marital conflict among married women at a significance level of 0.05. Conclusion: The changes in the average percentage of improvement observed with solution-focused single-session therapy suggest that this intervention can lead to immediate improvements in self-compassion, forgiveness, and marital conflict among married women. These findings underscore the potential importance of this type of therapy in enhancing marital relationships and improving the psychological well-being of married women.